PENGEMBANGAN MODUL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI PENYELENGGARAAN JENAZAH DI SMK NEGERI 1 BATIPUH - Yani, Nicha Andri; Masril, Masril; Trisoni, Ridwal (El -Hekam, 2019)
The problem of this research is the limitation of learning resource on Islamic Education and Character. In the learning process, the teacher only has book package of Islamic Education and character without presenting module, handout, LKS and other materials. The general purpose of this research is to find a module of Islamic education and character based on Contextual Teaching and Learning (CTL). Meanwhile, the specific purpose is to createthe valid and practical modules of Islamic education and character based on Contextual Teaching and Learning (CTL) so that it can be used by teacher and students in the school as a guiding in the learning process. The type of this research is developing research and also using 4-D models. It has 4 stages, they areÂ  define, design, developdan disseminate. The result of this research shows theeverage is 86 % from validity of module Islamic Education andÂ  Character based on Contextual Teaching and Learning (CTL) with very valid category.Meanwhile, the result of practicality from development of module islamic education and chacter based on Contextual Teaching and Learning (CTL) on material of organizing the corpse are obtained 90 % with very practical category.Based on the description above, it can be concluded that the development of PAI & BP Modules based on Contextual Teaching and Learning (CTL) on the material of organizing the corpse can be declared it is very valid and very practical so that it is suitable using for all teachers of Islamic Education and Character in the school.